The treatment of the wrestler's tactical preparation, based on requirements, contents and tactical means /El tratamiento de la preparación táctica del luchador, sustentado en exigencias, contenidos y medios tácticos - Liván Ariel Fernández Pérez; Osnel de Jesús Cedeño Linares; Jordan La Rosa Muñoz; Antonio de la Caridad Lanza Bravo (Universidad de Pinar del Río "Hermanos Saíz Montes de Oca", 2022)
In sport wrestling, tactical preparation is determinant for the achievement of competitive results, however, there are limitations in the recommended procedures for its development in training. The research faces this problem and its objective is to design a methodology for the treatment of the tactical preparation of juvenile wrestlers of Greco-Roman style in Villa Clara based on the demands, contents and tactical means. In the research, the current state of the conceptions used for the treatment of tactical preparation in wrestlers was diagnosed by means of surveys, observations of training sessions and competitions. From this, the elements that support the methodology were determined and its instrumental apparatus was organized based on the tactical demands, the tactical contents and the tactical means. After being evaluated by experts, its application in the juvenile Greco-Roman wrestling team of the Sports Initiation School of Villa Clara is exposed, where the effectiveness of the application of tactical situations is corroborated from the increase of individual tactical performance, causing the increase of sports results.